Interleukin-32 as a biomarker in rheumatic diseases: A narrative review - Kwon, Oh Chan; Park, Min-Chan; Kim, Yong-Gil (Frontiers in Immunology, 2023)
Interleukin-32 (IL-32) is an important cytokine involved in the innate and adaptive immune responses. The role of IL-32 has been studied in the context of various diseases. A growing body of research has investigated the role of IL-32 in rheumatic diseases including inflammatory arthritides (rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis) and connective tissue diseases (systemic lupus erythematosus, systemic sclerosis, granulomatosis and polyangiitis, and giant cell arteritis). IL-32 has been shown to play different roles according to the type of rheumatic diseases. Hence, the putative role of IL-32 as a biomarker is also different in each rheumatic disease: IL-32 could serve as a biomarker for disease activity in some diseases, whereas in other diseases it could be a biomarker for certain disease manifestations. In this narrative review, we summarize the associations between IL-32 and various rheumatic diseases and discuss the putative role of IL-32 as a biomarker in each disease.